DEVELOPMENT OF AN INSTRUMENT TO INVESTIGATE THE RELATIONSHIP BETWEEN THE RISKS RELATED TO EMPLOYERS’ AND CONSULTANTS’ CONTRACTUAL RESPONSIBILITIES AND CONTRACTORS’ WORK PROGRESS, CONSIDERING PROJECT CHARACTERISTICS AS A MODERATOR - Pan, Siaw Chin; Umi Kalsum Zolkafli @ Zulkifly,; Siaw Chuing Loo, (Journal of Surveying, Construction and Property, 2025)
There is a lack of studies examining the risks faced by contractors related to the non-adherence to contractual responsibilities by employers and consultants, and how project characteristics influence the impact of these risks on the contractors’ work progress. Due to the absence of a suitable survey instrument in past studies, this paper aims to introduce a valid survey to investigate the relationship between the risks related to the employers' and consultants’ contractual responsibilities and contractors’ work progress, and the moderating effect of project characteristics. A 43-item survey instrument was developed based on the PAM Contract 2018, past studies, and insights from industry experts. The instrument was validated through a qualitative approach (expert judgment) and a quantitative approach (content validity index). The validation method adopted in the study ensures that the items included in the proposed survey are clear and appropriately represent the key variables (employer-related risks, consultants-related risks, project characteristics, and contractors’ work progress). The final 40-item survey instrument has an average content validity index of 0.951, indicating excellent content validity. This paper presents the procedures adopted for developing and validating the survey instrument. The findings of this paper are valuable for future researchers in developing survey instruments.